Ariosto, the "Orlando Furioso" and English culture - Everson, Jane E. ca. 20./21. Jh; Hiscock, Andrew 1962-; Jossa, Stefano 1966-
Marking the fifth centenary of the publication of the first edition of the Italian masterpiece, Ariosto, the Orlando Furioso and English Culture, 1516-2016 brings together an international team of Renaissance scholars from a wide variety of disciplines to analyse in detail the diffuse impact which the epic poem had upon English culture from the Tudor century to the present day. Translated into English in the 1590s by Sir John Harington, godson of Elizabeth I, the influence of Ariosto's poem can be traced in literature, music and the visual arts, from Spenser and Milton to modern media adaptations. In addition, the collection reflects upon the ways in which successive editions and translations, examples of critical reception, rewritings and adaptations in different media (in particular opera) all shaped the rich and evolving understanding of the adventures of Orlando, Angelica, Medoro, Olympia, and Sacripante in the cultural and artistic production of England across the centuries
"... the conference from which this publication derives ..." (Acknowledgements)
Keywords: Ariosto, Ludovico -- 1474-1533 -- Orlando furioso; Geschichte 1516-2016; Englisch; Rezeption; Übersetzung; Literatur; England; Konferenzschrift -- 2016 -- London